Subjektive Theorien von Musikerinnen und Musikern zum Üben: Ein Beitrag an der Schnittstelle von Kognitionspsychologie - Bunte, Nicola; Scharlau, Ingrid (Popmusikforschung und Musikpädagogik)
This article reports on the findings of a qualitative interview study that investigated the individual ideas about practicing of nine musicians of different musical backgrounds, music genres, instruments, and learning biography. The findings reveal a variety of different aspects that are embedded in argumentative reasoning, and thus are analysed as subjective theories. According to differences in complexity with regards to content and argumentative structure we propose the following typification: 1) physical-technical constriction, 2) technique and interpretation centered type, and 3) creative-congnitive focus. A strict affiliation between these types and musical genre was not found.